From Containment to Rationalization : Increasing Public Expenditure Efficiency in France - Hallaert, Jean-Jacques.; Queyranne, Maximilien (Washington, D.C. : International Monetary Fund, 2016)
Achieving France's medium-term fiscal targets will require significant expenditure efforts. This paper identifies areas where there is scope for increasing expenditure efficiency, with a view to achieving higher quality and more sustainable fiscal consolidation. The methodology is based on a triple benchmarking. First, the level of public expenditure in different categories is compared to other European countries. Second, the impact of spending is assessed against other European countries. Third, the input mix is analyzed to understand what components are responsible for the level of spending and for the quality of outcomes This is done for various categories of spending and policies. Based on these results, the paper then provides policy options for expenditure reform in each of these areas, drawing on successful reform episodes in other countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet